2019
DOI: 10.1080/20008198.2018.1558707
|View full text |Cite
|
Sign up to set email alerts
|

Complicated grief and post-traumatic stress symptom profiles in bereaved earthquake survivors: a latent class analysis

Abstract: Background: Studies on mental health following disasters have primarily focused on post-traumatic stress disorder (PTSD), yet severe, enduring, and disabling grief [i.e. complicated grief (CG)] also appears relevant.Objective: The present study examines symptom profiles of PTSD and CG among bereaved Sichuan earthquake survivors 1 year after the disaster.Method: Self-report measures of demographic, disaster, and loss-related characteristics and symptoms of PTSD and CG were administered among 803 survivors (63% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
36
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 47 publications
5
36
0
9
Order By: Relevance
“…Building on earlier work-prior to the LCA research-showing that PGD, PTSD, and depression are among the most commonly observed disorders following bereavement [14], several prior studies have identified subgroups of bereaved people based on symptoms of PGD/ PCBD, PTSD, and/or depression. These studies mostly identified at least three classes, including a class with low symptom levels, a class with elevated PGD/PCBD (but not other) symptoms, and a class with elevated combinations of symptoms [15][16][17][18][19][20][21]. Based on this prior work, we expected different classes, including classes characterized by low symptoms, elevated PGD symptoms only, and elevated symptoms across all three symptom clusters.…”
Section: Introductionmentioning
confidence: 96%
“…Building on earlier work-prior to the LCA research-showing that PGD, PTSD, and depression are among the most commonly observed disorders following bereavement [14], several prior studies have identified subgroups of bereaved people based on symptoms of PGD/ PCBD, PTSD, and/or depression. These studies mostly identified at least three classes, including a class with low symptom levels, a class with elevated PGD/PCBD (but not other) symptoms, and a class with elevated combinations of symptoms [15][16][17][18][19][20][21]. Based on this prior work, we expected different classes, including classes characterized by low symptoms, elevated PGD symptoms only, and elevated symptoms across all three symptom clusters.…”
Section: Introductionmentioning
confidence: 96%
“…Consequently, as demonstrated in recent pioneering studies in Psychiatry Research, increased psychiatric complaints, including anxiety and depression, are common among the general public in COVID-19 affected areas (e.g., Cao et al, 2020). While increases in mental health problems following natural disasters and viral outbreaks have been previously documented, there is historically less attention for severe, disabling and protracted grief responses, termed complicated grief or prolonged grief (PG) (Eisma et al, 2019). This is at least partly due to the fact that, until recently, disturbed grief was not included as a disorder in psychiatric classification systems.…”
mentioning
confidence: 99%
“…First, disasters with many casualties generally result in higher levels of PG symptoms among bereaved survivors, than observed following other modes of death. Moreover, PG symptoms in these survivors are often distinct from comorbid disorders, such as post-traumatic stress disorder (PTSD) or depression (for a brief review: Eisma et al, 2019). For instance, one year after the Sichuan earthquake, latent class analyses demonstrated that approximately a quarter of bereaved survivors experienced high PTSD and PG symptom levels and another quarter exclusively experienced high PG symptoms (Eisma et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of recent studies have sought to investigate correlates of PGD and PTSD symptom profiles after loss by identifying distinct groups of individuals suffering from one of the disorders (15)(16)(17)(18)(19)(20)(21) using the proposed symptoms for PGD (22) or the DSM criteria for PTSD (23). One such study used latent class analysis (LCA) to investigate PGD and PTSD symptom profiles and their correlates in a sample of adult refugees who had lost a loved one (17) .…”
Section: Introductionmentioning
confidence: 99%